Growth in Women's Relative Wages and in Inequality Among Men: One Phenomenon or Two? - Welch, Finis (American Economic Review, 2000)
Although increased wage inequality among men during the past three decades has received more attention, the growth in women's wages has been equally remarkable. In fact, by one measure of inequality, the ninth-decile/median ratio, the proportional growth in inequality has moved in exact proportion with the female/male wage ratio. It is suggested that both result from expansion in the value of brains relative to brawn. There is no way of knowing the full story of growth in women's relative wages, and it is important not to dismiss the import of changing career patterns. As is evident in the panel data, increasing labor market participation must be important. So, too, are the implications that follow the movement of women from the home to the job.